Optimizing Internal Audit as a Pillar of Managerial Control: A Literature Review - Ni Made Candra Dewi (The Journal of Financial, Accounting, and Economics, 2025)
Internal audit plays a strategic role in managerial control, particularly in the face of the complexity and dynamics of the modern, uncertain business environment. This study aims to analyze the role, challenges, and optimization strategies of the internal audit function through a literature review approach. The main focus of this study is how internal audit contributes to the effectiveness of control systems, improving governance, and strengthening risk management within organizations. The findings of the literature review indicate that internal audit effectiveness is significantly influenced by factors such as auditor competence, level of independence, top management support, and the use of information technology in the audit process. In addition to highlighting critical success factors, this study also identified several key challenges in internal audit implementation, including limited human resources, resistance to change, and rapid regulatory and technological developments. Therefore, optimization strategies are needed, such as enhancing auditors' professional capacity, adopting data-driven audit technology, and strengthening communication between auditors and management. The study concludes that internal audit needs to transform from a traditional oversight function into a proactive, adaptive, and collaborative strategic partner in driving the achievement of organizational goals. The implications of this research provide direction for developing more relevant and competitive internal audit practices in the digital era.